Emprego de técnica cirúrgica e materiais adesivos diretos no fechamento de diastema - Okida, Ricardo Coelho [UNESP]; Okida, Daniela Secches da Silveira; Machado, Lucas Silveira [UNESP] (My University, 2011)
The following is a clinical case report of a patient whose main complaint was the presence of a generalized spacing in the anterior maxillary segment. After meticulous clinical analysis and discussions of the clinical procedures to be adopted, a labial frenectomy was our first choice, so that we could reduce the diastemas directly using composite resin. It was observed that the association of clinical and restorative procedures was capable of giving back shape, function and dental aesthetics, allowing to the young patient the satisfaction of smiling without any fear.

Relato de caso clínico de paciente que apresentava como queixa principal a presença de espaços generalizados no segmento anterior superior. Após meticulosas análises clínicas e discussões das condutas terapêuticas a serem adotadas, inicialmente, foi realizada uma cirurgia de frenectomia para possibilitar a realização dos procedimentos restauradores diretos com resina composta para diminuir os espaços presentes na região anterior. Observamos que a associação de procedimentos cirúrgicos e restauradores foram capazes de devolver a forma, a função e a estética dental, possibilitando à jovem paciente a satisfação de sorrir sem receios.
Association of cirurgic procedures with direct adhesive materials in closing diastemas
Keywords: Diastema; Labial frenum; Dental bonding; Diastema; Freio labial; Colagem dentária